The Influence of Human Resource Competence, Innovation, Digital Marketing, and Organizational Commitment on the Performance of MSMEs in Pekanbaru City - Tia Azrillia; Vera Oktari; Devi Safitri (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine the effect of Human Resources Competence, Innovation, Digital Marketing, and Organizational Commitment on MSME Performance in Pekanbaru City. The research method used is a quantitative research method, with a data collection method in the form of a questionnaire. The population in this study was the MSME in Pekanbaru City, totaling 26,684 MSME. The sample in this study was 100 respondents using a convenience sampling technique. Data analysis was carried out using Structural Equation Modeling–Partial Least Square (SEM-PLS) using SmartPLS software version 4.0.9.2 to process the data. The results of this study indicate that the variables of Human Resources Competence, Innovation, Digital Marketing, and Organizational Commitment have an effect on MSME Performance in Pekanbaru City.